Pulmonary rehabilitation in mild chronic obstructive pulmonary disease - Jácome, Cristina (2014)
Pulmonary Rehabilitation (PR) is a core component of the management of patients with moderate-to-very-severe chronic obstructive pulmonary disease (COPD). However, impairments in quadriceps muscle strength and health-related quality of life (HRQL) are already present in patients with mild COPD. Thus, there is a need to investigate if PR could also be beneficial to these patients. This study assessed the impact of PR on different health domains in patients with mild COPD. Twenty participants (66.1±10.8yrs; forced expiratory volume in one second 88.9±11.3% predicted) enrolled in a primary care PR program, with exercise training and psychoeducation (12 weeks). Dyspnea was assessed with the Modified British Medical Research Council questionnaire; functional balance with the Timed Up and Go test; muscle strength with the 10 repetition maximum testing; exercise tolerance with the 6-minute walking test and HRQL with the St. George's Respiratory Questionnaire (SGRQ). Significant effects were observed on participants' dyspnea (median 1 vs. 0.5; p=0.003), functional balance (7.7±1.4s vs. 6.6±1.1s; p=0.001), knee extensors strength (4.3±2.1kg vs. 6.7±1.7kg; p<0.001) and exercise tolerance (439±80.9m vs. 470.8±79.6m; p=0.001). With the exception of the SGRQ impact score (19.7±17.9 vs. 15.5±15.9; p=0.057), the symptoms (48.5±20.9 vs. 34.8±23.5), activities (48±23.6 vs. 33.3±26.4) and total (33.1±18.3 vs. 24.2±19.4) scores improved significantly with PR (p<0.001). Patients with mild COPD benefit from PR and may gain from being routinely included in these programs. Studies with more robust designs and with long-term follow-ups are needed to inform guidelines for PR in mild COPD.